Morfologia urbana na animação - Piccin, Priscila Schmeling [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The production and concept of the animation process adds not only technical aspects to it, but also the huge amount of detail and study of every single reference used to create that said animation. From costumes and fashion to urban morphology, those researches are needed for the creation of a final product that has a truth feeling to it, making the viewer feel like part of it and receive not only a literal aspect, but a conceptual feel from the project. Photos, maps, technical studies and much more are tools of trade when dealing with the animation process. The animators have to give attention to every single detail in order to make the production feel alive for the viewers, making the animations flow in a charming way. To analyse the inverse way of the animation process – from the final product to the sketch studies of the base reality from which it was based at- is a good way to comprehend the research line of the animators, and that’s the main focus of this project

A produção e concepção de uma animação englobam não apenas aspectos técnicos do próprio meio como também um grande e detalhado estudo de um material de referência. Desde costumes e moda até morfologia urbana, tais pesquisas são necessárias para a criação de um produto que transfira veracidades ao público, não de maneira literal, mas de maneira conceitual. Fotos, mapas, estudos técnicos entre outros são as ferramentas utilizadas pela equipe de animação para dar vida aos projetos. São pequenos detalhes que muitas vezes passam despercebidos ao público, mas que tornam as obras mais tácteis e charmosas. Analisar o sentido inverso - da animação para a concepção urbana de sua origem - é uma forma de compreender melhor o trabalho de pesquisa dos animadores, sendo este o foco principal do trabalho
Keywords: Aminação por computador; Arquitetura - Projetos; Morfologia urbana; Arquitetura urbana - animação por computador